2016
DOI: 10.15421/nvlvet6808
|View full text |Cite
|
Sign up to set email alerts
|

Застосування Кріопорошку «гарбуз» В Технології Сиркових Мас Різної Жирності

Abstract: Стан харчування населення – один із найважливіших факторів, що визначає здоров'я і збереження генофонду нації у забезпеченні збалансованого харчування. Використання рослинних біодобавок у цьому плані містить невичерпне джерело та ресурси. Використання кріопорошків, як фітодобавок до молочних продуктів, вміле їх поєднання несе у собі великі перспективи, як у соціальному, так і біолого–технологічному плані. Кріопорошки – це інноваційні продукти, що містять необхідні вітаміни і мікроелементи, створені самою приро… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In recent years, cryopowders have become very popular [5]. Authors Peresichny M., Korzun V. [6] showed that the introduction of various types of cryopowders in the form of fillers in fermented milk drinks allowed creating new types of drinks with therapeutic and prophylactic action, which had delicious taste and high sensory characteristics. The use of cryopowders for sweet dishes and products allowed enriching them with vitamins, minerals, dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cryopowders have become very popular [5]. Authors Peresichny M., Korzun V. [6] showed that the introduction of various types of cryopowders in the form of fillers in fermented milk drinks allowed creating new types of drinks with therapeutic and prophylactic action, which had delicious taste and high sensory characteristics. The use of cryopowders for sweet dishes and products allowed enriching them with vitamins, minerals, dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account modern difficult ecological conditions of Ukrainian regions, there is an acute necessity in improving the food structure of the population at the expanse of increasing the quality, biological value and taste characteristics of products [1][2][3]. The important direction in it is their enrichment with vitamins, mineral and immune substances, especially on the natural base [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the modern ecological condition, there is an acute need in improvement of the nutrition structure of population at the expanse of raising quality, biological value and gustatory characteristics of products [1][2][3]. The important direction at that is their enrichment with vitamins, mineral and immune substances, especially with ones on natural base [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The skillful combination of cryoadditives (as bioadditives) with "milk" base has great prospects in both bio-technological and social aspects. The cryopowders are wholesome for both children and adults [1]. It seems more attractive to use the natural vegetable bioadditives that include significant number of deficit microelements and other biologically active substances in cheese masses technology [1,6].…”
Section: Introductionmentioning
confidence: 99%